Active Surveillance for Avian Influenza Virus, Egypt, 2010–2012 - Kayali, Ghazi; Kandeil, Ahmed; El-Shesheny, Rabeh; Kayed, Ahmed S.; Gomaa, Mokhtar M.; Maatouq, Asmaa M.; Shehata, Mahmoud M.; Moatasim, Yassmin; Bagato, Ola; Cai, Zhipeng; Rubrum, Adam; Kutkat, Mohamed A.; et al. (Emerging infectious diseases, 2014)
Continuous circulation of influenza A(H5N1) virus among poultry in Egypt has created an epicenter in which the viruses evolve into newer subclades and continue to cause disease in humans. To detect influenza viruses in Egypt, since 2009 we have actively surveyed various regions and poultry production sectors. From August 2010 through January 2013, >11,000 swab samples were collected; 10% were positive by matrix gene reverse transcription PCR. During this period, subtype H9N2 viruses emerged, cocirculated with subtype H5N1 viruses, and frequently co-infected the same avian host. Genetic and antigenic analyses of viruses revealed that influenza A(H5N1) clade 2.2.1 viruses are dominant and that all subtype H9N2 viruses are G1-like. Cocirculation of different subtypes poses concern for potential reassortment. Avian influenza continues to threaten public and animal health in Egypt, and continuous surveillance for avian influenza virus is needed.